Quasi-Real Scenario of Reconfigurable Filtering Functions Antenna for UWB Communications - Medkour, Hicham; Zegadi, Ameur; Vandelle, Erika; Djadour, Imededdin; Phu, Vuong Tan (Elektronika ir Elektrotechnika, 2018)
In this paper, an Ultra Wide Band antenna with reconfigurable filtering-characteristic is proposed to overcome interferences problems in the frequency range 3.1 GHz–10.7 GHz. With dimensions of 35 x 35 mm2, the structure is simple, low–cost and possesses an operating bandwidth from 3 GHz to 12 GHz. Besides, it is easy to reconfigure this antenna to filter one, two or three interferences, in which the filtering is achieved by three slots of half wavelength created in the geometry, while the reconfiguration is achieved through four PIN diodes used to control the three slot’s effect. Considering the filtering action, this antenna can switch between eight distinct operational modes, which is the highest number compared to previous works. Design and analysis of the proposed configuration are done by two simulation software which are CST and HFSS. The acceptable agreement between the results obtained by both simulations proves the realistic working performance of the proposed structure. The present antenna is suitable for UWB communication applications, particularly; the which are suffering from interference issues with WiMAX 3.3 GHz–3.7 GHz, WLAN 5 GHz–5.3 GHz or ITU band 8 GHz–8.4 GHz. DOI: http://dx.doi.org/10.5755/j01.eie.24.5.21849